Economic effects of flood disaster among smallholder farmers in Kelantan, Malaysia - Jega, Abdussalam Adamu (2018)
Out all natural disasters flood remained the most common and frequent in most part of the world constituting the largest economic and social effect. Smallholder farmers who solely depend on agriculture for their livelihoods are the major vulnerable group to its cascading effect. Hence, this demonstrated the importance of governments’ policy responses in terms of mitigation and recovery to help in reducing flood damage and its social consequences. This study, therefore, investigates the economic effect of flood disaster among Kelantan state smallholder farmers and the level and/or extent of policy responses provided by governments in terms of mitigation and recovery, aimed at moderating/reducing flood disaster adverse effect on their livelihoods. The 2014/2015 flood disaster which was termed the most significant and largest recorded flood in the history of Kelantan state of Peninsular Malaysia, also declared as a ‘tsunami-like disaster by National Security Council (NSC) had affected about 70% of the villages who are mostly smallholder farming communities in the state. This thesis therefore, was guided by an integrated conceptual framework predominantly developed from disaster impact model and incorporated with a construct “livelihood outcomes” from the sustainable livelihoods approach (SLA) to explain how smallholder farmers are socially affected by flood disaster. For this study the framework consist of five variables, flood disaster characteristics as independent variables, livelihood outcomes (food security and income) as dependent variable, direct and indirect effect on agriculture as mediating variables, mitigation strategies and recovery resources as moderating variables and finally socioeconomic and demographic factors as control variables. A structured questionnaire was used to interview 385 affected smallholder farmers randomly selected from flood prone areas through a systematic sampling procedure. Descriptive analysis, paired sample t-test, ordinal logistic regression, Lorenz curve and structural equation modelling were applied in analysing the data using SPSS, Microsoft Excel, STATA and AMOS respectively. The descriptive findings of the flood disaster direct effect on smallholder farmers’ agriculture, revealed that the output of almost all crops, the value of livestock and agricultural assets, declined after being affected by 2014/2015 flood disaster. Hence, despite this flooding effect, 60.8% of the affected smallholder farmers were found be food secured during and after the disaster and their income was not adversely affected as indicated in the ordered logistic and Lorenz curve analysis. The structural equation modelling results also indicated that government policy response in terms of recovery has played a significant role in moderating the adverse flood disaster effect on smallholder farmer’s livelihood outcomes. This indicates that prompt government response and other stakeholders in terms of food aid supply, cash transfer, provision of agricultural productive assets and inputs the flood victims contributed a lot in alleviating flood disaster effect on their livelihood outcomes. However, mitigation strategies provided by the government in form of dams’ construction, embankments, levees etc. were found not sufficiently enough to prevent the flood disaster physical effect on their agricultural production activities and this indicates that government has paid more attention to reactive (recovery) than proactive (mitigation) measures. The mediation test results revealed that the flood disaster effect on smallholder farmer’s agriculture through crop and livestock losses, consequently disrupt their livelihood outcome but on a short-term basis. Based on these results, therefore, it is important to enhance mitigation strategies as a proactive measure, so as to save millions of ringgit from flood disaster effect on agriculture. It was also observed that the level of smallholder farmer’s pre and post adaptation strategies were almost moderately carried out, therefore it is important also to further enlighten smallholder farmers using their own resources to adequately undertake adaptation measures so as to complement government interventions against flood disaster. Finally, for study implications, first it could help policymakers to facilitate and improve on the flood disaster management practices to lessen/avoid future effects in the study area and also give an insight to academicians/researchers in applying and/or improving the model while assessing the effect of flood and other natural disasters in future research.